Urban wetlands: preservation and management of urban ecosystems - Koduru, Siddhartha; Dutta, Swati (2008)

(untitled)
Hyderabad had around 400 lakes a century ago that played a significant role in the urban ecology. They were habitats for a variety of flora and fauna and acted as microclimate stabilizers. Most of them had social, cultural and historical significance. They were natural sources of ground water recharge and flood prevention. But, today only 104 of them exist. Hyderabad has shortage of underground water, as it is located on the Deccan plateau formed of igneous rocks. Over the centuries, these water bodies served as flood cushions and rainwater storage tanks, assuring water for domestic use and agriculture for a period ranging between 6-8 months annually. But during the past 50 years, these wetlands have undergone tremendous deterioration due to over exploitation and improper management of lakeshore areas. Reducing output of water from these water bodies have made them even more vulnerable. Introduction of sewage and pollutants has degraded the water quality for sustenance of aquatic life and also pollution of underground water has been affecting the health of the society considerably. Added to this, there has been the increasing lacuna of development agencies and the growing reliability of consumers on packaged water that the situation has gone beyond repair in many cases. The seriousness of environmental deterioration and their implications were felt in the form of flash floods in 2000-2001, extreme underground water shortage, reduction in agricultural produce, spread of water borne diseases and loss of potential centers of tourism and recreation. The scope of the paper is to detail out the methodology adopted by the development agencies to restore and conserve these urban wetlands and water bodies under the technical guidance of national and international bodies and experts. Aspects dealt in this respect are their present status and surrounding physical conditions, fund mobilization, community participation, maintenance, etc. thereby generating a self-sustainable and integrated management plan.